Ventilation System Modelling and Turbulence Minimisation - WHALLEY, R. (2014)
In this feasibility study, a large scale ventilation system comprising spatially dispersed enclosed volumes, fans, ducting and airways is considered. Analytical procedures enabling the construction of simple, compact models including the relatively pointwise and significantly distributed system elements are proposed. Modeling accuracy, with the incorporation of the entrance and exit impedances and the airway, continuous energy storage and dissipation effects are emphasized. Output flow maximization, under quiescent operating conditions is investigated and the optimum relationships between the airway characteristic impedance, entrance and exit resistances are established. The minimization of the vibration and turbulence arising from the continuous compression/expansion effects arising from the input–output volume airflow difference is achieved, whilst simultaneously maximizing the output volume airflow. Variations in the parameter values are employed to confirm the effectiveness of operating under optimum conditions, for ventilation system airways with various dimensions and characteristics.